On planning sightseeing tours with TripBuilder. Issue 2 (March 2015) - Brilhante, Igo Ramalho; Macedo, Jose Antonio; Nardini, Franco Maria; Perego, Raffaele; Renso, Chiara
Highlights The formal problem of planning a tourist visit as a fully-automatic two-step process. An unsupervised method for mining common patterns of movements of tourists. A comprehensive evaluation of TripBuilder.